Perbedaan Ketidakwajaran Skor Berdasarkan Teori Respon Butir ditinjau dari Model Penskoran Jawaban Siswa SMP se Kota Palangka Raya - Sugiharto Sugiharto (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This study aims to know about the difference of unfair score based on item response theory referred to the model of students’ answers scoring of Junior High Schools throughout the city of Palangka Raya. The samples were taken from 17 state and private Junior High Schools throughout the city of Palangka Raya. Furthermore, the students’ answers were corrected by using scoring models, namely punishment score and correct score. Before doing the test to take the data, the data had to be validated first, both in the content and the empirical data. From the 40 test items, they have obtained 30 valid items. To obtain the proportion of fair score, it was used the estimation using BILOG-MG program. Furthermore, the data were analyzed with the different proportions (Z) of the two groups. The results of the data analysis showed that Zcount is -2.806, while Ztable is -1.65 so Zcount rank outside the receipt area of H0. It shows that the students with the scoring models of punishment score encompass the score that more than the scoring models of the correct score with a significant difference in the proportion. It can be concluded that the students who were corrected by using scoring models of punishment score have a fair index better than the fair index of the students were corrected by using scoring models of correct score.